Penentu Pilihan dDan Kepuasan Konsumen Terhadap Sayuran Organik di Kota Malang: Implikasi Untuk Strategi Pemasaran - Ramadhani, Festy Putri; Windiana, Livia; Aryanti, Nirmala Ayu (Universitas Galuh, 2026)
The growing public awareness of the importance of a healthy lifestyle has driven the rising trend of organic-based product consumption among communities in Malang. This shift has also influenced purchasing decisions, with health considerations emerging as a primary determinant. Consumer purchase decisions and satisfaction, however, are shaped not only by health awareness but also by the marketing strategies implemented by producers. This study aims to examine consumer perceptions of organic vegetables, customer knowledge, socio-cultural influences, product accessibility, value-added attributes, and price factors that affect consumer behavior and determine consumer satisfaction with organic vegetables in Malang City. A mixed-method approach was employed, integrating qualitative techniques through Focus Group Discussions (FGDs) and literature review with quantitative analysis using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected through in-depth interviews and surveys using purposive and incidental sampling in Lai Lai Supermarket, Superindo, and several organic vegetable markets in Malang. The research investigated factors including product, price, place, and promotion. Data analysis consisted of descriptive statistics, multiple linear regression, and SEM-PLS. Findings from the FGDs reveal that consumer knowledge of the health benefits of organic vegetables, social influences, product quality, and perceived high prices significantly shape purchasing decisions. The quantitative analysis confirms that all marketing mix variables exert a significant effect on customer satisfaction, with product and price being the most influential contributors. This study provides theoretical insights into consumer perception and satisfaction related to organic vegetables, and offers practical implications for agribusiness practitioners and stakeholders in developing more effective marketing strategies for organic vegetable products in Malang City.